ANALYSIS OF KIDNEY HISTOPATHOLOGY IN SEPSIS MODEL OF MICE (MUS MUSCULUS) WITH PREVENTIVE TREATMENT OF LEAF EXTRACT FROM 'DAUN KENTUT' PLANT (PAEDERIA FOETIDA L.) AGAINST ESCHERICHIA COLI INFECTION - Savitri, Lisa; Kasimo, Elfred Rinaldo; Krissanjaya, Rochmad; Sukmawati, Datin An Nisa; Juwita, Syntia Tanu; Kholis, Akbar Nur; Mosse1, Yosep (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Sepsis is a critical health concern characterized by organ dysfunction due to uncontrolled host reactions to infections. The prevalence of microorganisms causing sepsis varies, with Gram-positive bacteria and fungal sepsis gaining significance. Sepsis often leads to acute kidney injury (AKI), and its association with sepsis is known as sepsis-associated AKI (SA-AKI). The